The mediating effects of coping strategies between symptom clusters and quality of life in lung cancer patients undergoing immunotherapy - Xuying Yang; Jingcui Bai; Xiaohong Zhang (BMC Psychiatry)
Abstract Objective Immunotherapy has significantly improved the survival rates of lung cancer patients. However, prevalent adverse immune reactions associated with this treatment can detrimentally affect their quality of life. Coping strategies play a crucial role throughout the cancer treatment process. Consequently, this study hypothesised that coping strategies act as a mediating factor between symptom clusters and quality of life. This study intended to provide a theoretical foundation and empirical data to support the optimisation of coping strategies for lung cancer patients, thereby enhancing their overall quality of life. Method This study consisted of a cross-sectional survey. Data were collected using the Memorial Symptom Assessment Scale, the Medical Coping Modes Questionnaire, the Quality of Life Questionnaire-Lung Cancer 43, and a self-designed General Information Evaluation Form. The data were fitted, and the model was refined using the maximum likelihood estimation method. Additionally, the Bootstrap method was employed to assess mediating effects. Results In total, 240 participants completed the survey. During immunotherapy, lung cancer patients predominantly adopted the acceptance-resignation coping strategy, which served as a mediating factor between symptom clusters and quality of life. In contrast, the mediating effects of confrontation and avoidance coping strategies between symptom clusters and quality of life were not significant. Conclusion Both symptom clusters and the acceptance-resignation coping strategy negatively impacted quality of life, with acceptance-resignation serving as a mediating factor between symptom clusters and quality of life. Future research should focus on developing interventions for cognitive behaviour to improve coping strategies and quality of life throughout the disease trajectory.